2020
DOI: 10.5194/acp-2020-783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement report: Ice nucleating abilities of biomass burning, African dust, and sea spray aerosol particles over the Yucatan Peninsula

Abstract: Abstract. Most precipitation from deep clouds over the continents and in the intertropical convergence zone is strongly influenced by the presence of ice crystals, whose formation requires the presence of ice nucleating particles (INP). Although there are a large number of INP sources, the ice nucleating abilities of aerosol particles emitted from oceans, deserts, and wildfires are poorly described at tropical latitudes. To fill this gap in knowledge, the UNAM-MicroOrifice Uniform Deposit Impactor-Droplet Free… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Cerón et al (2002) reported large concentrations of Na, Cl, and Mg that originated from sea salt, when analyzing the composition of rainwater from the Yucatán Peninsula. The high levels of S can be associated with local anthropogenic activities such as vehicular, ship, and industrial emissions (e.g., Corbett and Fischbeck, 1997;Cerón-Bretón et al, 2018). Additionally, given the short distance between Mérida and the GoM, it is possible that dimethylsulfide (DMS) production from plankton in the GoM could be a natural source of S, as has been shown in other studies (e.g., Rosinski et al, 1988;Kloster et al, 2006;Vallina and Simó, 2007).…”
Section: Local Evidencementioning
confidence: 84%
See 1 more Smart Citation
“…Cerón et al (2002) reported large concentrations of Na, Cl, and Mg that originated from sea salt, when analyzing the composition of rainwater from the Yucatán Peninsula. The high levels of S can be associated with local anthropogenic activities such as vehicular, ship, and industrial emissions (e.g., Corbett and Fischbeck, 1997;Cerón-Bretón et al, 2018). Additionally, given the short distance between Mérida and the GoM, it is possible that dimethylsulfide (DMS) production from plankton in the GoM could be a natural source of S, as has been shown in other studies (e.g., Rosinski et al, 1988;Kloster et al, 2006;Vallina and Simó, 2007).…”
Section: Local Evidencementioning
confidence: 84%
“…If the foreign biological particles are opportunistic pathogens, they can cause a variety of diseases in the receptor regions, such as the Yucatán Peninsula. Finally, these particles can impact the development of precipitation and affect the regional hydrological cycle when they serve as efficient ice-nucleating particles (e.g., Rosinski et al, 1988;Córdoba et al, 2020).…”
Section: Discussionmentioning
confidence: 99%